Graphic Artist Hollis Claims Diverse Background. - Hopson, Lindit (Raton Range Raton, NM, 1991)
This article is about Charlotte Hollis and her graphic art.
Newspaper article + photograph of a drawing
Mater List Item # 69
File location is in the New Mexico File Cabinets
Keywords: Hollis, Charlotte; Hollis, Jim; University of New Mexico; Seton Museum; Philmont Scout Ranch; New Mexico Boys School; Artist Biography; Art; Stained Glass; Graphic Art; Indian Drawings; Screen Printing; Miami, New Mexico